Шляхи підвищення ефективності хірургічного лікування хворих з новоутвореннями легенів - Бойко, Валерій Володимирович; Кріцак, Василь Васильович; Краснояружський, Андрій Григорович; Грома, Василь Григорович (ТОВ "Ліга - Інформ", 2018)
Визначити ефективність ендоскопічної бронхосанації для профілактики до– та післяопераційних ускладнень у хворих з новоутвореннями легенів. Матеріали і методи. Вивчено ефективність ендоскопічної фотодинамічної терапії за розробленою авторами методикою з уведенням у трахеобронхіальне дерево водного розчину барвника метиленового синього в концентрації 0,04%, опроміненого лазером з довжиною хвилі 0,63 мкм, самостійної і в поєднанні зі стандартною протизапальною терапією як передопераційної підготовки трахеобронхіального дерева у хворих з раком легенів. У дослідження включено 181 пацієнта з раком легенів II–III стадії, морфологічно підтвердженим, та супутнім ендобронхітом. Результати. За даними аналізу титру і характеру патогенної мікрофлори в просвіті бронхіального дерева після проведеної передопераційної підготовки встановили, що у разі застосування самостійної ендоскопічної бронхосанації у 55 (87%) спостереженнях патогенної мікрофлори не було. У разі поєднання фотодинамічної бронхосанації зі стандартною терапією патогенну мікрофлору не виявлено у 52 хворих. У разі стандартної підготовки без використання лазерної терапії мікрофлори не виявили лише в 44,8% спостережень. Поряд з метаплазією слизової оболонки бронхів у ряду досліджуваних хворих визначали диспластичні зміни бронхіального епітелію різного ступеня вираженості. Самостійна ендоскопічна бронхосанація приводила до достовірного зниження загальної частоти дисплазії епітелію бронхів у хворих до 36,1%, у поєднанні зі стандартною протизапальною терапією – до 42,4%. Висновки. Застосування ендоскопічної фотодинамічної бронхосанації за запропонованою методикою в передопераційному періоді у хворих з метою корекції супутнього ендобронхіту як самостійної, так і в поєднанні зі стандартною протизапальною терапією приводить до зменшення частоти ендобронхіальних ускладнень після оперативного лікування раку легенів у порівнянні з контрольною групою. Ендоскопічна бронхосанація супроводжується значним зниженням вираженості ендоскопічних ознак супутнього ендобронхіту і поліпшенням мукоциліарного транспорту. За даними мікробіологічних тестів у 87 – 88% хворих спостерігали повну санацію бронхіального дерева та зникнення основних гістологічних критеріїв запалення, у 67,2 – 100% хворих – відновлення нормальної будови слизової оболонки бронхіального дерева.

Efficacy of endoscopic bronchosanation for prophylaxis of preoperative and postoperative complications in patients with pulmonary tumors. Маterials and methods. There was studied the efficacy of endoscopic photodynamic therapy in accordance to procedure, elaborated by the authors, including injection of the water solution of a methylene blue dye in concentration 0.04% into tracheobronchial tree, irradiated by laser with the wave length 0.63 mcm, independently and in conjunction with a standard anti–inflammatory therapy as preoperative preparation of tracheobronchial tree in patients, suffering pulmonary cancer. In the investigation 181 patients were included, suffering pulmonary cancer Stages II–III, morphologically confirmed, and with coexistent endobronchitis. Results. In accordance to analysis of the pathogenic microflora titer and character in lumen of bronchial tree after preoperative preparation there was established, that while application of independent endoscopic bronchosanation in 55 (87%) observations the pathogenic microflora was absent. While combination of photodynamical bronchosanation in accordance to standard therapy a pathogenic microflora was not revealed in 52 patients. While conduction of a standard preparation without application of a laser therapy microflora was not revealed only in 44.8% observations. Together with the bronchial mucosa metaplasia in some investigated patients the dysplastic changes of bronchial epithelium of various severity degree were registered. Independent endoscopic bronchosanation have leaded to trustworthy lowering of a general rate of the bronchial epithelial dysplasia in the patients tо 36.1%, together with standard anti–inflammatory therapy – tо 42.4%. Conclusion. Application of endoscopic photodynamic bronchosanation in accordance to the proposed procedure in preoperative period in the patients with objective to correct a concomitant endobronchitis, as independent option or together with standard anti–inflammatory therapy, leads to reduction of the endobronchial complications rate after operative treatment for pulmonary cancer, comparing with a control group. Еndoscopic bronchosanation is accompanied by significant lowering of severity of endoscopic signs of coexistent endobronchitits and improvement of mucociliary transport. In accordance to microbiological tests in 87 – 88% of patients a complete sanation of bronchial tree and elimination of main histological criteria of inflammation were noted, while in 67.2 – 100% patients – restoration of normal structure of the bronchial tree mucosa.
Ways of enhancement of the surgical treatment efficacy in treatment of patients, suffering pulmonary tumors
Keywords: передопераційна підготовка; ендоскопічна фотодинамічна терапія; післяопераційні ускладнення; preoperative preparation; endoscopic photodynamic therapy; postoperative complications